Evaluation of two cryprotectans and three curves of programable freezing in semen cryopreservation of Brycon henni (Pisces: Characidae) - Restrepo-Betancur, Giovanni (2017)
The aim of this study was to evaluate the cryopreservation of Brycon henni semen using three programmable freezing curves and two permeable cryoprotectants. Semen of 80 males were diluted in medium supplemented with ethylene glycol (EG) or dimethylsulfoxide (DMSO), and cryopreserved in semen straws using three programmable freezing curves: slow (66 min, -0.42 °C/min), medium (43.3 min, -0.6 °C/min) and ultra-rapid (7.7 min, -5.19 °C/min). After one month of storage, semen was thawed and motility was evaluated through a class analysis system (SCA®) and sperm vitality (EV) by fluorescence microscopy with SYBR14/IP probes. For statistical analysis, generalized linear models (GLM) were adjusted and means compared by the Tukey test. The medium and ultrarapid velocity curves showed higher and equivalent values for total motility, progressive motility, and linear velocity of sperm (p<0.05). Sperm vitality was better in the medium velocity curve (52.4 ± 8.6%) in comparison with the ultra-rapid (43.0 ± 19.4%) and slow (29.0 ± 11.8%) curves (p<0.05). EG showed greater sperm vitality (p<0.05). It is concluded that freezing of sabaleta semen (B. henni) by a medium velocity programmable freezing curve and ethylene glycol as cryoprotectant allows better results of post-thaw semen quality.